A multi-component bioactive formulation involving hyaluronic acid and melatonin combined with nano-hydroxyapatite and grape seed extract for enamel remineralization: an in vitro assessment - Demirci, Aysenur Ertunc; Erci, Fatih; Ozenen, Didem Ozdemir; Isildak, Ibrahim (IOP Publishing Ltd, 2025)
Objective. Structural loss in sound enamel and dentin adversely affects quality of life, emphasizing the need for rapid and effective treatment. Early carious lesions-characterized by subsurface demineralization without surface cavitation-are fully reversible when detected early. This study aimed to evaluate the in vitro remineralization potential of a novel formulation containing hyaluronic acid (HA), melatonin (MEL), nano-hydroxyapatite (nHAp), and grape seed extract (GSE, Vitis vinifera). Materials and Methods. Sixty bovine enamel samples were divided into six groups: four treatment groups ([nHAp-GSE], HA_[nHAp-GSE], MEL_[nHAp-GSE], HA-MEL_[nHAp-GSE]), and positive and negative controls. Artificial carious lesions were created and treated using a 7-day pH cycling model. Surface microhardness recovery (SMHR), surface roughness (optical profilometry), morphology (SEM), FTIR spectroscopy, elemental composition and Ca/P ratio (EDS), and crystallinity (XRD) were assesed. Statistical analyses included one-way ANOVA and Tukey HSD (p < 0.05). Results. HA-MEL_[nHAp-GSE] showed the highest SMHR (66.2%), followed by MEL_[nHAp-GSE] (53.5%) and HA_[nHAp-GSE] (45.0%). [nHAp-GSE] showed 26.9%; controls showed 35.7% (positive) and 3.2% (negative) (p < 0.05). EDS confirmed group-specific differences in Ca/P ratios, while XRD analysis demonstrated that all formulations retained crystalline hydroxyapatite consistent with reference patterns. Conclusions. HA and MEL-enhanced formulations showpromising potential for non-fluoride-based early caries management, supported by bond structure, crystallinity, and enamel surface analysis. Further clinical studies are warranted. Clinical Relevance. This study introduces a novel, fluoride-free formulation for the non-invasive management of early carious lesions. The combination of HA acid and MEL significantly enhances remineralization, offering a biocompatible, patient-friendly, and esthetically favorable approach in preventive and restorative dentistry.
Keywords: remineralization; nano-hydroxyapatite; grape seed extract; hyaluronic acid; melatonin; FLUORIDE; LESIONS; CARIES; DEMINERALIZATION; DIFFERENTIATION; PROLIFERATION; EFFICACY; Materials Science